2012
DOI: 10.1021/jp3099472
|View full text |Cite
|
Sign up to set email alerts
|

Probing Structural and Motional Features of the C-Terminal Part of the Human Centrin 2/P17-XPC Microcrystalline Complex by Solid-State NMR Spectroscopy

Abstract: Insight into structural and motional features of the Cterminal part of the Human Centrin 2 in complex with the peptide P17-XPC was obtained by using complementary solid-state NMR methods. We demonstrate that the experimental conditions and procedures of sample crystallization determine the quality of solid-state NMR spectra and the internal mobility of the protein. 13 C− 13 C and 15 N− 15 N correlation spectra reveal intra-and inter-residue dipolar connectivities and provide partial, site-specific assignments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…We have demonstrated that recoupling schemes such as Phase Alternated Recoupling Irradiation Schemes (PARIS) (Weingarth et al 2009b, c) and PARIS-xy (Weingarth et al 2010) permit one to reach similar peak amplitudes (±10 %) for chemically different sites on time scales as short as a few hundreds of milliseconds. We have previously used these pulse schemes to record sensitive 2D correlation spectra of microcrystalline proteins (Weingarth et al 2009c;Herbert-Pucheta et al 2012b), amyloid fibrils (Weingarth et al 2011b) and mixtures of crystallographic forms (Herbert-Pucheta et al 2011), and to restore the symmetry in 2D homonuclear correlation experiments of simple amino acids (Herbert-Pucheta et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that recoupling schemes such as Phase Alternated Recoupling Irradiation Schemes (PARIS) (Weingarth et al 2009b, c) and PARIS-xy (Weingarth et al 2010) permit one to reach similar peak amplitudes (±10 %) for chemically different sites on time scales as short as a few hundreds of milliseconds. We have previously used these pulse schemes to record sensitive 2D correlation spectra of microcrystalline proteins (Weingarth et al 2009c;Herbert-Pucheta et al 2012b), amyloid fibrils (Weingarth et al 2011b) and mixtures of crystallographic forms (Herbert-Pucheta et al 2011), and to restore the symmetry in 2D homonuclear correlation experiments of simple amino acids (Herbert-Pucheta et al 2012a).…”
Section: Introductionmentioning
confidence: 99%